I expected to be pain free: a qualitative study exploring athletes’ expectations and experiences of care received by sports chiropractors - Evan Eindhoven; Alex Lee; Peter Stilwell; Silvano Mior (Chiropractic & Manual Therapies, 2022)
Abstract Background Knowledge about patient satisfaction and experience with care they receive can guide practitioners in establishing doctor-patient relationships and improve health outcomes. Although evidence suggests high patient satisfaction with chiropractic care in general, there is limited understanding of the expectations and experiences of athletes receiving sports chiropractic care. Objective To explore the athletes’ expectations and experiences with care received from sports chiropractors, and their perceptions of relevant areas of future research. Methods A qualitative study was conducted through an interpretivist lens exploring the perspectives of elite and competitive athletes receiving care from sports chiropractors in Canada. Participants were purposively recruited and interviewed until saturation was reached. Two research team members independently analyzed the interview transcripts using a conventional approach to content analysis. Content was inductively coded and discussed by the research team to generate categories. Results We interviewed 18 participants between December 2018 and March 2020, 14 were national level athletes participating in sports ranging from paddling to combat sports. Reported reasons for seeking care included acute care, injury prevention, enhancing performance and maintenance care. Generated categories were organized under topics of experience with care, expectations of care, and research agenda. Participants experienced a variety of interventions, reassurance, varying treatment times, and reported positive impact on their athletic performance. They expected musculoskeletal assessment and treatment including at and beyond the injury site, symptom improvement, good communication and expertise from the chiropractor. Some participants suggested interpersonal and interprofessional communication can be improved, in particular the level of collaboration with other members of their health care team. Overall, participants reported a high level of trust and satisfaction with care received from sports chiropractors. From our participants’ perspective, suggested areas of research should focus on injury mechanics and prevention, impact of care on performance, and interprofessional collaboration. Conclusions In general, participants were very satisfied with care. Overall, participants’ expectations and experiences aligned but changed over time. Addressing the findings of this study can be used to enhance the quality of care provided to athletes from sports chiropractors, as well as inform future research agendas. Further work assessing if athletes in other competitive levels have similar experiences and expectations is needed.